Basel III compliance and bank resilience: An analysis of the effects of macroeconomic factors and profitability on the performance of Indonesian banks - Hayati, Restu; Rachmawati, Eka Nuraini; Suriyanti, Linda Hetri (Journal of Accounting and Investment, 2026)
Research aims: This study examines the impact of Basel III prudential ratios (Tier 1 capital ratio, Liquidity Coverage Ratio proxy, and Net Stable Funding Ratio proxy) on bank profitability in Indonesia, as well as the moderating role of macroeconomic factors (GDP growth and inflation).Design/Methodology/Approach: The study utilizes panel data from 63 Indonesian commercial banks over the period 2011–2022. A bank fixed effects regression model with robust standard errors clustered at the bank level is employed. Four progressive specifications are tested to assess the direct effects of prudential ratios, bank-specific controls, macroeconomic variables, and their interactions.Research findings: The Tier 1 capital ratio consistently exerts a positive and significant effect on Return on Assets (ROA), indicating that higher capital adequacy supports profitability. Liquidity proxies have a limited direct impact, consistent with evidence that the NSFR often serves as a non-binding constraint in Indonesia. Macroeconomic factors play a moderating role, with GDP growth attenuating the capital-profitability relationship and inflation reinforcing it. Robustness checks excluding the NSFR proxy or the COVID-19 period confirm the stability of these results.Theoretical contribution/Originality: This study extends the Basel III literature by demonstrating that regulatory effects on bank profitability are conditional on macroeconomic conditions in an emerging market context. It provides evidence of asymmetric moderation, where growth cycles may encourage risk-shifting while inflation enhances capital benefits.Practitioner/Policy implication: Regulators should prioritize capital adequacy enforcement while calibrating liquidity requirements to avoid undue profitability costs. Banks can optimize performance by maintaining flexible capital buffers in response to macroeconomic fluctuations. Policymakers may consider countercyclical adjustments to enhance resilience without compromising earnings.